2002
DOI: 10.1159/000066074
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transtympanic Endoscopy of the Middle Ear in the Diagnosis of Perilymphatic Fistula in Patients with Sensorineural Hearing Loss or Vertigo

Abstract: Background: The diagnosis of perilymphatic fistula (PLF) is often difficult, and therefore the condition can be overlooked. Tympanoscopy presents an alternative procedure for visualising the middle ear anatomy, and it may help to diagnose PLF. Aim: The aim of this study was to evaluate the use of middle ear endoscopy in establishing the diagnosis of PLF and in defining its incidence in patients with sensorineural hearing loss and/or vertigo and tinnitus. Subjects and Methods: Two hundred and sixty-five patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
5
0
7
Order By: Relevance
“…Karhuketo and Puhakka [62] have endoscopically repaired an round window fistula in a diver. Selmani and colleagues [63] endoscoped one ear of two hundred and sixty-five patients with Meniere's disease, recurrent vertigo, progressive hearing loss, sudden deafness, otosclerosis, and suspected PLF. In general the round window could nearly always be viewed by a 5 degree rigid scope and the fissula ante fenestram edge of the oval window by a 25 degree scope.…”
Section: Operative Confirmation Of Plfmentioning
confidence: 99%
“…Karhuketo and Puhakka [62] have endoscopically repaired an round window fistula in a diver. Selmani and colleagues [63] endoscoped one ear of two hundred and sixty-five patients with Meniere's disease, recurrent vertigo, progressive hearing loss, sudden deafness, otosclerosis, and suspected PLF. In general the round window could nearly always be viewed by a 5 degree rigid scope and the fissula ante fenestram edge of the oval window by a 25 degree scope.…”
Section: Operative Confirmation Of Plfmentioning
confidence: 99%
“…focused their study on the detection of perilymphatic fistula and not on hearing results after successful sealing of the round window membrane. 24 Additionally, all patients underwent exploratory tympanotomy by endoscopy, regardless of the cause of the hearing loss. This study's design did not meet our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…There are a few retrospective studies that analyzed hearing after tympanotomy [14,15,20]. Selmani et al, who performed an endosopic inspection of the middle ear cavity, observed no perilymphatic fistula in 265 cases of patients with SSNHL and vertigo [21]. With respect to the well-established microsurgery of the middle ear and the possible infection during a middle ear endoscopy, we prefer the better visualization of the round window membrane via the operation microscope.…”
Section: Discussionmentioning
confidence: 99%